2020
DOI: 10.1542/peds.2020-0961
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection and Other Clinical Characteristics of COVID-19 in Children

Abstract: BACKGROUND AND OBJECTIVES: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a newly identified pathogen that mainly spreads by droplets. Most published studies have been focused on adult patients with coronavirus disease 2019 (COVID-19), but data concerning pediatric patients are limited. In this study, we aimed to determine epidemiological characteristics and clinical features of pediatric patients with COVID-19. METHODS: … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
252
5
23

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(301 citation statements)
references
References 18 publications
21
252
5
23
Order By: Relevance
“…On the other hand, co-infection can increase the severity of symptoms of both diseases in these cases, in which managing of this state is essential and critical in certain groups such as pregnant women, the elderly, and even children. Studies reported a high SARS-CoV-2 and influenza virus co-infection rate in children that highpoints the importance of COVID-19 screening, particularly during the prevalence of seasonal influenza and other respiratory disorders [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, co-infection can increase the severity of symptoms of both diseases in these cases, in which managing of this state is essential and critical in certain groups such as pregnant women, the elderly, and even children. Studies reported a high SARS-CoV-2 and influenza virus co-infection rate in children that highpoints the importance of COVID-19 screening, particularly during the prevalence of seasonal influenza and other respiratory disorders [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…High fever in our patient could be caused by ileus complications due to uid sequestration to the third cavity which results in dehydration and may be accompanied by bacterial translocation [10]. It might be also caused by the body's reaction to the SARS-CoV-2 infection [11][12][13]. In addition, shortness of breath in our patient might be caused by abdominal distension due to bowel dilatation [14] or by SARS-CoV-2 infection of the lungs [15].…”
Section: Discussionmentioning
confidence: 76%
“…Thirteen reports included in the present study described fecal nucleic acid examination ( Table 2), The positive rate of fecal nucleic acid testing in COVID-19 patients was 85.8% (91/106). In reports from China 19,27,29,34,41,52 , the positive rate of all stool samples tested was close to or reached 100%. Additionally, 71.2% (52/73) were still positive for fecal nucleic acid after the respiratory tract specimens turned negative, 45.2% (33/73) were fecal nucleic acid-positive one week after the respiratory tract specimen was nucleic acid-negative, and 34.2% (25/73) were fecal nucleic acid-positive two weeks after a respiratory tract nucleic acid negative test.…”
Section: Fecal Testing For Viral Nucleic Acidmentioning
confidence: 81%